2019
DOI: 10.1055/s-0039-1690713
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective Preparation and Reactions of Chiral Secondary Alkyllithiums

Abstract: The preparation of chiral non-stabilized open-chain alkyl­lithium reagents prepared from the corresponding chiral secondary alkyl iodides and their subsequent transmetalation to the corresponding secondary alkylcopper or alkylzinc derivatives is reviewed. These new organometallic reagents allow the stereoselective preparation of a broad range of chiral molecules.1 Introduction2 Stereoselective Preparation of Secondary Alkyllithiums3 Preparation of Stereodefined Secondary Alkylcopper Reagents4 Preparation of St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…The enantioselective preparation of carbon-sulfur bonds was briefly examined since it proceeded also directly with chiral secondary alkyllithiums. 6 We observed that the coupling of ( R )- or ( S )-5h and syn -5d with MeSO 2 SMe (6k) led to the thioethers ( R )- or ( S )-4o and syn -4p in up to 85% yield, but moderate stereoselectivity (up to 78% ee or dr = 93 : 7). However, phosphorus electrophiles such as Ph 2 PCl (6l) reacted with high stereoretention with chiral Grignard reagents.…”
Section: Resultsmentioning
confidence: 82%
See 3 more Smart Citations
“…The enantioselective preparation of carbon-sulfur bonds was briefly examined since it proceeded also directly with chiral secondary alkyllithiums. 6 We observed that the coupling of ( R )- or ( S )-5h and syn -5d with MeSO 2 SMe (6k) led to the thioethers ( R )- or ( S )-4o and syn -4p in up to 85% yield, but moderate stereoselectivity (up to 78% ee or dr = 93 : 7). However, phosphorus electrophiles such as Ph 2 PCl (6l) reacted with high stereoretention with chiral Grignard reagents.…”
Section: Resultsmentioning
confidence: 82%
“…−50 °C for ca. 1 h and in comparison with the corresponding alkyllithium reagents (configurationally stable only below −100 °C for some minutes) 6 were better suited for synthetic applications.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, secondary and tertiary amines of types 4 and 5 can be prepared via these electrophilic amination reactions using various functionalized organozinc reagents of type 6 (Scheme 2). Besides, we will also cover in this short review novel stereoselective cross-couplings of organozinc reagents involving stereoselective I/Li-exchange reactions 5 as well as regioselective magnesiations of N-aryl azoles and related aromatic and heterocyclic substrates 6 followed by Negishi crosscouplings after transmetalation with ZnCl2 or Cu-catalyzed cross-couplings.…”
Section: Introductionmentioning
confidence: 99%